Ring Alternative Loops and their Loop Rings (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
In 1983, a few examples of Moufang loops whose loop rings are alternative, but not associative, were discovered. Since that time, there has been a great deal of worle devoted to the study of such loops and to their loop rings. This paper is a survey of some of the more important results in this still relatively young area.